Development of a soccer simulation protocol to include repeated sprints and agility - Stone, K. J.; Oliver, J. L.; Hughes, M. G.; Stembridge, M. R.; Newcombe, D. J. (International Journal of Sports Physiology and Performance, 2011)
Existing procedures for the simulation of soccer match play fail to incorporate multidirectional and repeated-sprint activities, even though these movements are considered fundamental to match play. In the current study, selected physiological and performance responses were assessed during an adapted version of an existing soccer simulation protocol. Mean heart rates of 163 ± 14 beats/min, mean blood lactates of 4.9 ± 2.3 mmol/L and decrements in single-sprint and repeated-sprint performances were observed. The presented adaptations to an existing soccer simulation protocol better reflect the movement characteristics as well as the physiological and performance responses of soccer match play.